ASSESSMENT OF IN VIVO LOADING HISTORY OF THE PATELLOFEMORAL JOINT- A STUDY COMBINING PATELLAR POSITION, TILT, ALIGNMENT AND BONE SPECT/CT TRACER UPTAKE/DISTRIBUTION PATTERNS. Issue 10 (10th June 2013) - Hirschmann Michael, Tobias; Schön, Stephan; Afifi, Faik; Rasch, Helmut; Testa, Enrique Adrian; Friederich, Niklaus; Arnold, Markus
Abstract : Introduction: SPECT/CT could be used to evaluate the in vivo loading pattern of the patellofemoral joint before and after realignment surgery. The purpose of this study is to investigate, whether the patella position (height and tilt) influences the intensity values as well as the distribution pattern of SPECT/CT tracer uptake in the patellofemoral joint. Methods: 99mTc-HDP-SPECT/CT and conventional radiographs of consecutive 84 knees were prospectively obtained. Lateral radiographs were then analysed in terms of patellar height, the Insall-Salvati index and the modified Insall-Salvati index. Skyline views were analysed measuring the lateral patellofemoral angle according to Laurin. On long leg radiographs the mechanical leg alignment was classified as varus, valgus or neutral. 99mTc-HDP-SPECT/CT images were analysed for each anatomical region using a previously validated SPECT/CT localisation and grading algorithm. Mean, standard deviation, minimum and maximum of grading for each area of the localization scheme were recorded using a semiquantitative colour-coded grading scale (0–10). Nonparametric Spearman correlation coefficients were used to correlate the patella height, the lateral patellar angle and leg alignment measurements with the intensity of tracer uptake in each area of interest. Chi square statistics were used for categorical data. The level of statistical significance was p<0.05. Results: 16 (19%) knees showed valgus, 34 (40.5%) varus and 34 (40.5%) neutral mechanical alignment. A lower patella position correlated significantly with higher 99mTc-HDP SPECT/CT tracer uptake in all patellar and lateral femoral regions (p<0.001). A higher lateral patellar angle correlated significantly with higher 99mTc-HDP tracer uptake in the superior lateral femoral parts and the tibial tubercle. The intensity of 99mTc-HDP SPECT/CT tracer uptake on the medial part of the patellofemoral joint significantly correlated with mechanical varus alignment of the knee (p<0.05). The intensity of 99mTc-HDP tracer uptake on the lateral part of the patellofemoral joint significantly correlated with mechanical valgus alignment of the knee (p<0.05). Conclusions: The intensity and distribution of the SPECT/CT significantly correlated with patella infera and patellar tilt angle, measured in conventional radiographs. Hence, SPECT/CT should be considered as imaging modality for evaluating patients with patellofemoral disorders and for follow-up of patients after patellofemoral realignment procedures.